CHALLENGES FACED BY PARENTS OFHIGHLY SENSITIVE CHILDREN AND SOLUTIONS - Shimron, Bar (E-Journal VFU, 2025)
Lead Section: Challenges Faced by Parents of Highly Sensitive Children Parents of Highly Sensitive Children (HSC) encounter distinctive challenges that significantly shape their parenting experience and family dynamics. HSC often exhibit heightened emotional and sensory sensitivity, which can lead to intense emotional reactions and require parents to navigate complex emotional landscapes. This phenomenon is notable due to its increasing recognition in psychological research and its implications for both the well-being of parents and the development of their children. As these challenges become more understood, the need for effective strategies and support systems for these families grows ever more pressing (Highly Sensitive Child, n.d, Eggshell Therapy, n.d.) One of the most profound challenges parents face is emotional overwhelm, stemming from the demands of managing their child’s intense emotional responses. This emotional drain, compounded by societal pressures to juggle parenting with work and other responsibilities, can lead to feelings of isolation and burnout (Highly Sensitive Child, n.d) Additionally, many parents report a lack of social support, which further exacerbates their feelings of loneliness. The modern tendency towards individualism in parenting often leaves these parents with minimal opportunities for connection and shared experiences with others, highlighting the need for communal support networks (Highly Sensitive Child, n.d, Moore, n.d). Navigating educational needs presents another significant hurdle. HSC often thrive in tailored educational environments that accommodate their unique sensitivities; however, traditional educational settings can be ill-suited to their requirements, pushing parents to advocate fiercely for appropriate resources and learning environments (Highly Sensitive Child, n.d, Eggshell Therapy, n.d.) Furthermore, the influence of familial dynamics and the parents’ own upbringing can complicate their ability to provide the nurturing atmosphere that HSC need. Many struggle with ingrained patterns of behavior from their past, which may hinder their parenting effectiveness and contribute to feelings of guilt or inadequacy (Little Otter, n.d, Smith, 2021) In response to these challenges, numerous strategies and resources are emerging to support parents of HSC. These include creating structured and calming environments, implementing self-regulation techniques, and seeking professional guidance. The growing body of research on HSC emphasizes the importance of community support, effective parenting strategies, and educational accommodations as critical components for fostering healthy development in highly sensitive children (Safe Solutions, n.d.). ,Eggshell Therapy, n.d., Boulanger, 2022). As awareness and understanding of these issues expand, so too does the potential for positive change in the lives of families with HSC.